Tuning the capacitance of graphene-based materials as negative electrode materials for supercapacitor applications - Azman, Nur Hawa Nabilah; Lim, Xiang Chuan; Sulaiman, Yusran (Elsevier Ltd, 2025)
Graphene-based materials (GMs) were hydrothermally fabricated for supercapacitors, with an in-depth investigation of the doping of nitrogen and sulfur into the GMs as negative electrodes being reported for the first time. XRD analysis revealed that graphene oxide (GO) was reduced to form the graphene derivatives, and the GMs exhibited a typical wrinkled sheet morphology. The doping of heteroatoms into the lattice structure of reduced graphene oxide (RGO) was confirmed through the Fourier-transform infrared spectroscopy (FTIR), energy dispersive X-ray (EDX), thermogravimetric analysis (TGA) and Raman analysis. The electrochemical performance, evaluated using 1 M LiOH, showed that S-doped reduced graphene oxide (SRGO) achieved the highest specific capacitance (Csp) of 339.07 F g−1. Despite containing only 0.38% sulfur in its structure, SRGO exhibited the highest pseudocapacitance contribution (Cp) of 40.37 %, as well as low charge transfer resistance and a promising specific surface area (SSA) of 148.68 m2 g−1, resulting in its superior Csp. Conversely, N, S co-doped reduced graphene oxide (NSRGO) demonstrated the lowest Csp (209.17 F g−1), which was attributed to its relatively low SSA (95.27 m2 g−1) and Cp (25.25 %) compared to RGO and SRGO. Notably, RGO had the greatest SSA (153.40 m2 g−1) among the GMs, leading to a relatively high Csp of 253.48 F g−1. Thus, SRGO emerges as a highly promising negative electrode material for supercapacitors.